Constructing porous organic polymer with hydroxyquinoline as electrochemical-active unit for high-performance supercapacitor. (24th January 2019) - Chen, Jian; Du, Cheng; Zhang, Yan; Wei, Wei; Wan, Liu; Xie, Mingjiang; Tian, Zhengfang
Abstract: As one type of electrode materials for supercapacitor, porous organic polymer usually suffers from poor rate performance and inferior cycling stability because of the low electrochemical stability. Herein, a porous organic polymer with hydroxyquinoline as electrochemical-active unit is synthesized by one-step polymerization reaction between perylene, 8-hydroxyquinoline and chloroform. The obtained porous polymer owns large surface area (221.4 m 2  g −1 ), porous structure, abundant redox active sites (hydroxyquinoline) and exhibits a superior supercapacitive performance with a high specific capacitance of 522.0 F g −1 (at 1.0 A g −1 ) and an unprecedented rate capability (65.5% capacitance retention from 1 to 10 A g −1 ) in a three-electrode configuration. The assembled symmetric supercapacitor based on the designed porous polymer demonstrates a high energy density of 29.8 Wh kg −1 at a power density of 0.16 kW kg −1 in the voltage range 0–1.6 V and good cycling stability of 71.2% capacity retained after 10000 cycles, makes the derived porous polymer a promising electrode material for the high-performance energy storage device. Graphical abstract: Image 1 Highlights: PyrOxin-POP with hierarchical porous structure was firstly fabricated. Hydroxyquinoline as electrochemical-active unit generates pseudocapacitance. PyrOxin-POP exhibits large capacity of 552 F g −1 and good rate capability of 65.5%. PyrOxin-POP achieves an unprecedented cycling stability of 71.2% after 10000 cycles. The symmetric supercapacitor device shows a high energy density of 29.8 Wh kg −1 .